2003
DOI: 10.1083/jcb.200305145
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-mediated endocytosis in AP-2–depleted cells

Abstract: We have used RNA interference to knock down the AP-2 μ2 subunit and clathrin heavy chain to undetectable levels in HeLaM cells. Clathrin-coated pits associated with the plasma membrane were still present in the AP-2–depleted cells, but they were 12-fold less abundant than in control cells. No clathrin-coated pits or vesicles could be detected in the clathrin-depleted cells, and post-Golgi membrane compartments were swollen. Receptor-mediated endocytosis of transferrin was severely inhibited in both clathrin- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

94
706
2
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 640 publications
(807 citation statements)
references
References 35 publications
94
706
2
5
Order By: Relevance
“…5), indicating that γ1 and γ2 are mostly expressed as part of an AP-1 complex. In fact, it has been previously demonstrated that in the absence of one of the subunits, the respective AP complex becomes unstable and disassembles, resulting in decreased levels of the other subunits Meyer et al, 2000;Motley et al, 2003;Peden et al, 2002). Moreover, as for γ1, interaction of Nef with γ2 absolutely requires co-expression of the σ1 subunit (Mattera et al, 2011;and our results, data not shown).…”
Section: Discussionsupporting
confidence: 63%
“…5), indicating that γ1 and γ2 are mostly expressed as part of an AP-1 complex. In fact, it has been previously demonstrated that in the absence of one of the subunits, the respective AP complex becomes unstable and disassembles, resulting in decreased levels of the other subunits Meyer et al, 2000;Motley et al, 2003;Peden et al, 2002). Moreover, as for γ1, interaction of Nef with γ2 absolutely requires co-expression of the σ1 subunit (Mattera et al, 2011;and our results, data not shown).…”
Section: Discussionsupporting
confidence: 63%
“…Pulldown assays have also suggested that LL 814/815 and LL 855/856 bind AP-1 (Wyss et al, 2001), but no previous evidence has suggested that either of these motifs bind AP-2 or that the C terminal LL motif can mediate endocytosis of HIV Env. To examine the functional activities of these signals in more detail, we used siRNA against the 2 subunit of AP-2, which have been demonstrated to inhibit AP-2-mediated endocytosis (Fraile-Ramos et al, 2003;Motley et al, 2003). HeLa cells expressing CD4-Env constructs were treated with the siRNA, and the levels of 2 expression were analyzed 56 h after nucleofection by Western blot.…”
Section: Endocytosis Of Cd4/hiv Env Chimeras Is Dependent On the Clatmentioning
confidence: 99%
“…siRNAs against clathrin and 1A have been described (Hirst et al, 2003;Motley et al, 2003). HeLa cells were transfected using Oligofectamine (Invitrogen, Carlsbad, CA) as specified by the manufacturer.…”
Section: Rna Interferencementioning
confidence: 99%